A Discrete Wavelet Transform based STATCOM Compensated Transmission Line - K Mishra, S.; N Tripathy, L.; C Swain, S. (International Journal of Engineering and Technology, 2018)
This paper describes the Discrete Wavelet transform (DWT) applied for classification and detection of fault with respect to the position of the Static Synchronous Compensator (STATCOM).Â  STATCOM is positioned at mid-point of the transmission line. The reactive power injection or absorption (i.e shifting phase voltage with respect to bus voltage) depends upon the apparent impedance during the fault. The current signals of each phase are retrieved from both sending and receiving end of three phase transmission line synchronously. It starts processing through DWT to acquire spectral energy (SE) content of each phase current signals from both end of the transmission line. Differential spectral energy (DSE) of each phase current signals (i.e SE of current signal recovered from sending end minus SE of current signal recovered at receiving end) of transmission lines is used to record the fault configuration.Â